Transcription analysis of softening-related genes during postharvest of papaya fruit (Carica papaya L. ‘Pococí’ hybrid) - Zerpa Catanho, Dessireé Patricia (2017)
Fruit of Carica papaya L. (papaya) has several post-harvest problems mainly caused by quick softening that reduces its shelf life. This softening is directly related to degradation and modification of cell wall oligosaccharides. Therefore, it is important to study, understand and, eventually, regulate the softening process of this fruit to increase its shelf life. This work aims at looking for correlations between transcription patterns of four genes potentially involved in papaya fruit softening with postharvest treatments and the softening process. Papaya fruit (‘Pococí’ hybrid) were treated with ethylene (275–300 mL L−1), 1-methylcyclopropene (1-MCP, 300 nL L−1), or not treated, as control. Fruit were subsequently stored for eleven days at 18–20 °C and 95% relative humidity. During the evaluation period, firmness (N) and color (CIE L*, a* and b*) of pulp and peel were determined; pH, titratable acidity (TA) and total soluble solids (TSS) of pulp were also measured; in addition, transcription patterns of polygalacturonase, endoxylanase, pectinesterase and expansin genes were determined by real time PCR. Treatments showed differences in terms of firmness, color, pH, TA, ripening index and accumulation of transcripts of some genes. Transcription of polygalacturonase and endoxylanase genes correlated negatively with firmness of pulp and peel; whereas pectinesterase gene was positively correlated with peel firmness. No correlation with transcription of the expansin gene analyzed was found. Our results also suggest that polygalacturonase and endoxylanase correlated negatively with papaya fruit firmness and that 1-MCP treatment repressed and reduced the expression of these two genes, respectively. According to these results, silencing genes that encode polygalacturonases or endoxylanases might be a potential strategy to confirm their crucial role on papaya ripening.